Serpulidae (Annelida: Polychaeta) from Hong Kong - Sun, Yanan; Hove, Harry A. Ten; Qiu, Jian-Wen (Zootaxa, 2012)
Serpulidae (Sabellida, Annelida) is a large group of sedentary polychaetes that live in the calcareous tubes they secrete.In addition to being an important component of marine hard-bottom benthic communities, serpulids include several eco-nomically important invasive and/or fouling species. In this paper we describe the serpulids from Hong Kong, based onspecimens collected from a coral community, a fish farm, a public pier and a shipping channel. Seventeen serpulid taxabelonging to five genera are recorded. The most diverse genus in the present material is Hydroides (9 species), followedby Spirobranchus (5 taxa). The highest diversity (13 taxa) is found on dead coral skeleton. One species, Spirobranchustetraceros, is associated with live corals in high density. For each taxon, the habitat, distribution and morphological fea-tures are described. Including literature records, 20 taxa of serpulids have been reported from Hong Kong. An identification key to all these recorded taxa is provided.